Physical parameters and biological factors affect the abscopal effect of combining radiotherapy with immunotherapy: an update on preclinical works - Ren, Wangcai; Wen, Jialing; Guo, Gang; Gu, Wenchao; Zhang, Shenke; Liu, Chang; Osada, Kensuke; Shimokawa, Takashi; Wang, Qiaojuan; Wang, Yue; Tu, Xuanzhang; Li, Chen; et al. (Frontiers in Public Health, 2025)
In the process of radiotherapy for cancer patients, there is an extremely low probability phenomenon that the distal tumor/metastasis away from the irradiation field undergoes regression after localized radiation therapy, which is called the abscopal effect. Enhancing the incidence of this phenomenon possesses profound significance for the investigation of metastatic cancer treatment. Currently, the underlying mechanisms of the abscopal effect remain unclear. Radiation-induced immunogenic cell death is considered one of the potential mechanisms for the abscopal effect. From this perspective, we explored how physical parameters and biological factors influence this process. Differences between patients with respect to physical factors and intrinsic biological factors that activate the immune response (acquired factors) may affect the induction of the abscopal effect.